Fast High-Resolution Simulation of the Gross Slip Wear of Axially Symmetric Contacts. Issue 1 (2nd January 2016) - Dimaki, A. V.; Dmitriev, A. I.; Menga, N.; Papangelo, A.; Ciavarella, M.; Popov, V. L.
ABSTRACT: In the present article, we study the development of a wear profile in an axially symmetric contact under conditions of gross slip and assumption of the Reye-Archard wear criterion. Simulations are carried out using the method of dimensionality reduction and a full finite element method (FEM) formulation. The calculation time of the proposed model is several orders lower than that of FEM-based models and allows for much higher spatial resolution.